Targeting phosphoglycerate kinases by tatridin A, a natural sesquiterpenoid endowed with anti-cancer activity, using a proteomic platform - Ferraro, Giusy; Voli, Antonia; Mozzicafreddo, Matteo; Pollastro, Federica; Tosco, Alessandra; Monti, Maria Chiara (Frontiers in Molecular Biosciences, 2023)
Tatridin A (TatA) is a germacrane sesquiterpenoid containing one E-double bond and one Z-double bond in its 10-membered ring, which is fused to a 3-methylene-dihydrofuran-2-one moiety. Tatridin A bioactivity has been poorly investigated despite its interesting chemical structure. Here, a functional proteomic platform was adapted to disclose its most reliable targets in leukemia monocytic cells, and phosphoglycerate kinases were recognized as the most affine enzymes. Through a combination of limited proteolysis and molecular docking, it has been discovered that tatridin A interacts with the active domains of phosphoglycerate kinase 1, altering its hinge region, and it can be accountable for tatridin A inhibition potency on enzyme activity. A more detailed tatridin A biological profile showed that it is also fully active against gastric cancer cells, downregulating the mRNA levels of chemokine receptor 4 and β-catenin and inhibiting the invasiveness of living KATO III cells as a direct consequence of phosphoglycerate kinase 1 antagonism.